Reverse osmosis desalination and reclamation : control of colloidal and biofouling - Chong, Tzyy Haur (2008)
The focus of this thesis work was on the fundamentals of colloidal and biofouling in reverse osmosis (RO) desalination and reclamation. A novel sodium chloride tracer response technique coupled with ultrasonic technique was employed to monitor the progress of fouling by silica colloids, alginic acid and Pseudomonas fluorescens. This study provided an insight into the interplay between critical flux, concentration polarization or CP (through the enhanced osmotic pressure effect) and fouling. In colloidal fouling, critical flux determined the deposition of particles on the membrane surface. The build up of deposit layer caused an additional hydraulic resistance as well as the cake enhanced osmotic pressure (CEOP) effect, which could be the predominant contributor in the membrane performance loss. Whereas in biofouling, it was postulated that the role of CP was to control the level of nutrient for the growth of biofilm, which in turn caused the biofilm enhanced osmotic pressure (BEOP) phenomenon.